Exposure To Presidential Candidate News In Online Media And The Knowledge Level Of Young Voters In The 2019 Indonesian Election - Mulyadi, Urip; Mubarok, Mubarok; Triyono, Agus (Jurnal Ilmiah Komunikasi Makna, 2025)
Young voters who have just entered the voting age do not yet have a broad political reach to determine where they should vote and online media is one of the tools to reach them. This study aims to determine the significant relationship between news exposure about presidential candidates in online media with the level of choice of young voters in the 2019 election. This study is a type of explanatory quantitative research using the positivism paradigm. Data collection was carried out using questionnaires distributed to 100 respondents in Semarang City using purposive sampling techniques. Data calculation in this study uses Spearman Rank correlation analysis using the IMB SPSS application as an aid to conduct several statistical data tests. The results of this study indicate that all calculated questionnaire items are declared valid because the calculated r> r table (0.195), and are also declared reliable with a value above 0.600. The Spearman Rank correlation analysis test shows that there is a significant relationship between the Level of Media Exposure (X1), the Level of Media Attention (X2) and the Level of Knowledge of young voters in the 2019 election. (Y) of 0.000<0.05. There is a strong relationship between the variable level of media exposure and the level of choice of beginners in the 2019 presidential election of 0.624 . There is a strong relationship between the variable level of media attention and the level of choice of beginners in the 2019 presidential election of 0.580 . Thus, it can be concluded that the level of media exposure and the level of media attention have a significant relationship with the level of knowledge of beginners in the 2019 election.